1993
DOI: 10.1080/07391102.1993.10508021
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transitions of Poly(dl-dC) in Aqueous Solution as Studied by Ultraviolet Resonance Raman Spectroscopy

Abstract: Poly( dl-dC) in aqueous solution can undergo different equilibrium geometries, which strongly depend on salt nature and concentrations. These equilibrium structures have been monitored by resonance Raman spectroscopy (RRS) measurements in the ultraviolet region, i. e. by using 257 and 281 nm laser excitation wavelengths which favor the resonance enhancement of the Raman contributions from inosine and cytosine residues of poly( dl-dC), respectively. Spectral changes depending on the NaCI concentration and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Addition of decimillimolar NiCl2, however, transforms poly(dI-dC) * poly (dI-dC) into a Z-form (Fig. 11, B and inset B), as originally observed by CD spectroscopy in NaCl + NiCl2 and then confirmed by Raman spectroscopy (Miskovsky et al, 1993). The Z-form CD spectrum contains a positive band at 285 nm, a negative one at 270 nm, a strong positive band at 240 nm, and a deep negative band at 203 nm.…”
Section: Poly(dl-dc) Poly(dl-dc)supporting
confidence: 65%
“…Addition of decimillimolar NiCl2, however, transforms poly(dI-dC) * poly (dI-dC) into a Z-form (Fig. 11, B and inset B), as originally observed by CD spectroscopy in NaCl + NiCl2 and then confirmed by Raman spectroscopy (Miskovsky et al, 1993). The Z-form CD spectrum contains a positive band at 285 nm, a negative one at 270 nm, a strong positive band at 240 nm, and a deep negative band at 203 nm.…”
Section: Poly(dl-dc) Poly(dl-dc)supporting
confidence: 65%
“…In contrast, the Raman bands at 991, 1297, 1381, and 1532 cm –1 , which correspond to vibrational modes of cytosine localized near the glycosidic bond, experience an intensity decrease when dC 20 assembles with CPT (Figures b and S10). Previous work has shown that those base vibrations are affected by the deoxyribose ring puckering and the glycosidic bond orientation defined by the torsion angle (χ). , The conformational sensitivity of the in-plane base vibrations derives from vibrational coupling with the adjacent C(1′)-H bend from the deoxyribose ring (see Figure S10e). Therefore, the changes observed in peak amplitude are likely associated with a transition in sugar puckering and alteration of the torsional angle between the cytosine and the deoxyribose, induced by specific interactions between dC 20 and CPT that are absent in CPT/dA 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Modes in this region result from vibrational motions of the imidazole moiety of the hypoxanthine ring coupled with C 8 OH bending motions and are expected to be reflective of the substituent at the N 9 position. 29,32 The sensitivity of these modes to ribose conformation is not unexpected as normal mode calculations of hypoxanthine, 9-methylinosine, and inosine have shown that the nature of the N 9 substituent can dramatically affect the frequency of modes with significant N 9 vibrational motions. 24,25 Vibrational motions of the phosphate backbone have been shown to be strongly indicative of DNA…”
Section: Poly (Ri) Ribosyl Ring Conformationmentioning
confidence: 97%
“…Similarly, the intensity of the 1350 cm Ϫ1 band differs markedly in the low temperature spectra of the two cationic forms (Figures 8 and 9). This region of the spectrum is strongly sensitive to B 3 Z helix transitions of poly(dI-dC), 32 and the differences observed between the Na ϩ and K ϩ forms of poly(rI) are attributed to differences in ribosyl and backbone conformation. Modes in this region result from vibrational motions of the imidazole moiety of the hypoxanthine ring coupled with C 8 OH bending motions and are expected to be reflective of the substituent at the N 9 position.…”
Section: Poly (Ri) Ribosyl Ring Conformationmentioning
confidence: 98%